Liver Stiffness Measured by Shear-wave Elastography for Evaluating Intrahepatic Portal Hypertension in Children. Issue 6 (June 2017) - Yoon, Hee Mang; Kim, So Yeon; Kim, Kyung Mo; Oh, Seak Hee; Ko, Gi-Young; Park, Yangsoon; Lee, Jin Seong; Jung, Ah Young; Cho, Young Ah
ABSTRACT: Objectives: The aim of the study was to correlate liver stiffness (LS) and hepatic venous-pressure gradient (HVPG) and to evaluate the diagnostic performance of shear-wave elastography (SWE) for predicting clinically significant portal hypertension in children with suspected liver diseases, in consideration of the reliability criteria. Methods: We identified 33 SWEs from 32 children who underwent HVPG measurement within 2 weeks between June 2012 and October 2015. The correlation between LS and HVPG was assessed. The diagnostic performance for predicting clinically significant portal hypertension (HVPG ≥ 10 mmHg) was assessed using the receiver-operating characteristic curve. Reliable measurement was evaluated based on the coefficient of variation (CV). Results: LS was significantly correlated with HVPG (r = 0.742, P  < 0.001). The area under the receiver-operating characteristic curve for predicting clinically significant portal hypertension was 0.914, and the best cutoff value of 18.4 kPa showed sensitivity of 87.5% and specificity of 84.0%. LS measurements having CV ⩽ 0.2 were significantly correlated with HVPG (r = 0.774, P  < .001), whereas those having CV > 0.2 did not show a significant correlation with HVPG (r = 0.598, P  = 0.089). Conclusions: SWE had excellent diagnostic performance for predicting clinically significant portal hypertension in children with suspected liver diseases. LS measurements having CV ⩽ 0.2 may possibly be used as a reliability criterion in SWE measurement. Abstract : Supplemental Digital Content is available in the text